2021
DOI: 10.1248/bpb.b21-00247
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Oxytocin System to Ameliorate Early Life Depressive-Like Behaviors in Maternally-Separated Rats

Abstract: Oxytocin (OXT) -"the love hormone"has been involved in the anti-depressant activity of some selective serotonin reuptake inhibitors (SSRIs). The exact mechanism underlying the OXT pathway in depression is not fully clear. This study aimed to investigate the effect of OXT analogue, carbetocin (CBT) and the SSRI, escitalopram (ESCIT) on depressive-like behaviors following maternal separation (MS). It is worthy to mention that intranasal CBT has been approved by FDA for Prader-Willi syndrome. Adolescent Wistar al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…In our MS model, rats exhibited anxiety-like behaviors in adolescence ( Figures 1B–E ), which is consistent with other studies that used the same animal model ( Banqueri et al, 2017 ; Auth et al, 2018 ). Studies have shown that MS results in an elevated stress response and depressive-like behavior in adolescent rats, which is consistent with our study ( Yang et al, 2016 ; Hu et al, 2017 ; Kim H. B. et al, 2020 ; Abdelwahab et al, 2021 ). Additionally, our results showed that MS rats exhibited depressive-like behavior in adulthood ( Figures 1F,G ), which confirmed the findings of previous studies showing that MS leads to depression in adulthood ( Arborelius et al, 2004 ; Vetulani, 2013 ; Masrour et al, 2018 ; Ruiz et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our MS model, rats exhibited anxiety-like behaviors in adolescence ( Figures 1B–E ), which is consistent with other studies that used the same animal model ( Banqueri et al, 2017 ; Auth et al, 2018 ). Studies have shown that MS results in an elevated stress response and depressive-like behavior in adolescent rats, which is consistent with our study ( Yang et al, 2016 ; Hu et al, 2017 ; Kim H. B. et al, 2020 ; Abdelwahab et al, 2021 ). Additionally, our results showed that MS rats exhibited depressive-like behavior in adulthood ( Figures 1F,G ), which confirmed the findings of previous studies showing that MS leads to depression in adulthood ( Arborelius et al, 2004 ; Vetulani, 2013 ; Masrour et al, 2018 ; Ruiz et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…� Panel B appears similar to Fig 5B in [2]. � Panel D appears similar to Fig 6E in [2] with the exception of an area in the center of the panels which appears different.…”
supporting
confidence: 60%
“…Owing to the concerns about similarities with previously published content [2], published in 2021 by The Pharmaceutical Society of Japan [2], which is not offered under a CC BY license, Figs 4C, 5B-5D, 5G-5H, 6D and 6K-6L are excluded from this article's [1] license. At the time of retraction, the article [1] was republished to note these exclusions in the legends of Figs 4-6 and the article's copyright statement.…”
mentioning
confidence: 99%
“…The regulation of serotonergic function and HPA axis may mediate the antidepressant mechanism of OXT. Increased the expression of 5-hydroxytryptamine receptors and serotonin transporter of hippocampus correlated with oxytocin levels in a MS induced animal model of depression [ 129 ]. But OXT exerted a synergistic function of antidepressant efficacy, such as increasing SSRI sensitivity by regulating Integrin β3 (ITGB3) and Close homolog of L1 protein (CHL1) in BDNF expression [ 130 ].…”
Section: Introductionmentioning
confidence: 99%